2013
DOI: 10.1093/humrep/det272
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes of children born after frozen-thawed embryo transfer: a Nordic cohort study from the CoNARTaS group

Abstract: Perinatal outcomes in this large population-based cohort of children born after FET from three Nordic countries compared with fresh IVF and ICSI and spontaneous conception were in agreement with the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
244
5
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(286 citation statements)
references
References 34 publications
32
244
5
5
Order By: Relevance
“…These analyses indicate that frozen embryo state [4][5][6][7][8][9][10][11][12][13] is associated with an increased risk for LGA, and blastocyst embryo stage is associated with a decreased risk for SGA. The magnitude of the increase we found in the 2nd birthweight in the fresh/frozen pairs of siblings of +222 g is in accord with prior studies (+244 g 4 in an Australian population, +250 g 10 and +286 g 6 in Danish populations), and far exceeds the +81 g attributable only to an increase in parity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These analyses indicate that frozen embryo state [4][5][6][7][8][9][10][11][12][13] is associated with an increased risk for LGA, and blastocyst embryo stage is associated with a decreased risk for SGA. The magnitude of the increase we found in the 2nd birthweight in the fresh/frozen pairs of siblings of +222 g is in accord with prior studies (+244 g 4 in an Australian population, +250 g 10 and +286 g 6 in Danish populations), and far exceeds the +81 g attributable only to an increase in parity.…”
Section: Discussionmentioning
confidence: 88%
“…Prior studies have also consistently reported an excess of large-for-gestational age (LGA) birthweights among children born from frozen embryos; [4][5][6][7][8][9][10][11][12] longer embryo culture of fresh embryos has also been implicated as a potential cause of LGA [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that singletons born after FET have a perinatal outcome more comparable to those born after natural conception than to those born after fresh embryo transfer (fresh ET), having higher birth weight and less pregnancy complications [2][3][4][5][6][7][8][9][10]. However, higher risk for birth of a singleton being large for gestational age (LGA) has been revealed after FET [2,3,7,8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Among those undergoing IVF, the results between fresh and frozen embryo transfers (FET) in obstetric perinatal outcome terms are still unclear [57][58][59]. A systematic review and meta-analysis based on 11 observational studies concluded that after transferring frozen-thawed embryos, singleton pregnancies resulted in a lower risk of antepartum hemorrhage (RR = 0.…”
Section: Freeze-all-why?mentioning
confidence: 99%